Barriers and opportunities - Ramos, Ana (2023)
Based on the concepts, discussions and criticisms previously presented, this chapter alms to: (i) explore, from a methodological point of view, how it is possible to empirically investigate the continuous and bidirectional interaction between planning and assessment; and (ii) examine, in detail, the baniers and opportunities inherent to this type of studies. The bidirectional feedback between planning-assessment is exposed from a theoretical perspective to a practical understanding. Thus, it is presented an innovative design capable of operationalising the ideas presented throughout this book. Such design includes the building of randomized contrast groups and the use of assessment instruments, like the Game Performance Anaiysis System (GPAI), which can be adapted over time depending on what is pianned on a daily basls. Furthermore, given the need to interpret the context, longitudinal investlgations are suggested, as change implies time, as well as the use of interpretive approaches, since there is an urgent need to understand the reason behind the change. Finally, the barriers and opportunities that this type of lnvestigation entails are presented and debated. A final reflection hlghllghts the quality of information coming from this renewed research model and, ln consequence, the added value it provides to enrich the pedagogical process in the most diverse educational contexts.